Sprint cycling performance and asymmetry - Rannama, I.; Port, K.; Bazanov, B.; Pedak, K. (Journal of Human Sport & Exercise, 2015)
The purpose of this study was to examine the asymmetries in cyclist`s lower limbs strength and in the pedalling kinematics during a seated sprinting test and to identify the relationships between asymmetries and maximal cycling power. 16 competitive road cyclists (20.6±3.7 yrs., 181.5±5.0 cm, 74.8±7.0 kg) performed 10 Sec isokinetic maximum power test with cadence 120 RPM. The asymmetry of kinematic patterns of cyclist`s upper and lower body during pedalling was registered. Separately isokinetic peak torque (PT) of main lover limbs joint were measured at angular speeds 60, 180 and 240°/s. The differences in kinematic patterns and isokinetic PT values between two limbs were analysed for descriptive and inferential statistics (relative share in %, correlations and regression between asymmetry values and cycling power). Conclusion: The highest asymmetries were found in cyclist`s upper body kinematics and at the same time the most symmetrical were knee extensors strength values, but both parameters were negatively and significantly correlated with the performance of sprint cycling. By combining the leg extensors muscular strength with asymmetry of knee extensors strength and trunk kinematics the explanatory power of multiple regressions increased markedly from 0.68 to 0.92.